Association of Engineering and Shipbuilding Draughtsmen - Notes made from wireless bulletins (?) (page 15)
"Association of Engineering and Shipbuilding Draughtsmen - Notes made from wireless bulletins (?) (page 15)" [g0973015.jpg], n.d.